Work Commitment and Organizational Culture - Rafika Bestri; Ummi Kalsum; Nurhizrah Gistituati (Department of Guidance and Counseling, FIP, Undiksha, 2022)
Humans are resources that are assets in the organization. Humans have roles and functions that cannot be replaced by other resources even in technological improvements in science. Humans are an important factor in the development and progress of an organization. Because only humans have the ability to think critically (critical thinking), communicate (communication), collaborate (collaboration) and be creative (creativity). These human capabilities are needed by the organization in analyzing positions, analyzing organizational needs, managing existing resources (Man, Money and Material), making plans and other functions. In addition to this, organizations also need people who are dedicated, have good performance and are able to bind themselves to the vision and mission of the organization for the achievement of the goals of the organization. Therefore, in realizing a quality organization, people who are also qualified and have a high work commitment are needed. The purpose of this study was to find out how the competence and commitment to work in the organization at the Regional VIII Education Office Branch Office, Mentawai Islands Regency. This research is a qualitative research in the form of a case study. Data collection in this study was carried out using participatory observation techniques, interviews and documentation. The data is processed by using source triangulation technique. The findings of this study state 1) Low work commitment due to low competence. 2) Work commitment results in low performance. 3) Low work commitment causes the organizational culture to become less good.